2010
DOI: 10.1007/s11046-010-9366-6
|View full text |Cite
|
Sign up to set email alerts
|

Serological Evidence of Paracoccidioides brasiliensis Infection in Chickens from Paraná and Mato Grosso do Sul States, Brazil

Abstract: The objective of this study was to detect antibodies against Paracoccidioides brasiliensis in free-range and caged chickens Gallus domesticus. Initially, the humoral immune response of two chickens immunized with P. brasiliensis was evaluated. Both animals showed the production of antibodies to gp43, the major P. brasiliensis antigen. The seroepidemiological survey was conducted in chickens from the Pantanal region in Mato Grosso do Sul State (free-range n = 40) and from northern region of Paraná State (free-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Epidemiological studies of PCM in domestic and wild animals have been based mainly on immunological reactions using crude paracoccidioidin and purified gp43 as antigens [5][6][7][8][9][10][11][12][13][14][15][16]32]. Previously, our research group showed high rates of gp43 ELISA positivity in dogs [6], horses [9], sheep [12], goats [13], pigs [29], rabbits [30] and wild monkeys [15] from Paraná State, Brazil.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epidemiological studies of PCM in domestic and wild animals have been based mainly on immunological reactions using crude paracoccidioidin and purified gp43 as antigens [5][6][7][8][9][10][11][12][13][14][15][16]32]. Previously, our research group showed high rates of gp43 ELISA positivity in dogs [6], horses [9], sheep [12], goats [13], pigs [29], rabbits [30] and wild monkeys [15] from Paraná State, Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…presence in endemic areas. Infection by P. brasiliensis has been reported in domestic and wild animals such as dogs [5][6][7], horses in Uruguay and in Brazil [8,9], cows in Colombia and Brazil [10,11], sheep, goats and chickens in Brazil [12][13][14], and monkeys [15] and armadillos in Brazil [16]. P. brasiliensis isolates were obtained from soil samples in Argentina [17], Venezuela [18] and Brazil [19].…”
Section: Introductionmentioning
confidence: 99%
“…No signiϐicant difference was observed in relation to sex as observed in other seroepidemiological studies carried out by our group to evaluate paracoccidioiomycosis infection in dogs, monkeys and chickens (Ono et al 2001, Silveira et al 2006, Corte et al 2007, Oliveira et al 2011.…”
Section: Discussionmentioning
confidence: 46%
“…Epidemiological studies have shown that paracoccidioidomycosis occurs in several species of domestic and wild animals such as dogs (Mós & Fava-Netto 1974, Ono et al 2001, Silveira et al 2006, Canteros et al 2010, Fontana et al 2010, cows (Silveira et al 2008), horses (Conti Diaz et al 1972, Costa & Fava-Netto 1978, Corte et al 2009), armadillos (Fernandes et al 2004), sheep (Costa & Fava-Netto 1978, Oliveira et al 2011, monkeys (Corte et al 2007), guinea pigs, raccoons, grisons, porcupine (Richini-Pereira et al 2008) and chickens (Gonçalves et al 2011). The fungus was also isolated from armadillos (Naiff et al 1986, Bagagli et al 1998, Corredor et al 1999, Silva-Vergara et al 2000 penguin faeces (Gezuele 1989), and recently, natural paracoccidioidomycosis was reported in two dogs (Ricci et al 2004, Farias et al 2011), a cat (Gonzalez et al 2010) and a two-toed sloth (Trejo-Chávez et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The infection of domestic and wild animals by P. brasiliensis occurs frequently as reported in several epidemiological studies with dogs, horses, cattle, sheep, chickens, goats coati‐mundi, felines, monkeys and armadillos, although natural disease was reported only in two dogs, a cat and a southern two‐toed sloth …”
Section: Introductionmentioning
confidence: 98%